2003
DOI: 10.1074/jbc.m306201200
|View full text |Cite
|
Sign up to set email alerts
|

An Oxidized Purine Nucleoside Triphosphatase, MTH1, Suppresses Cell Death Caused by Oxidative Stress

Abstract: MTH1 hydrolyzes oxidized purine nucleoside triphosphates such as 8-oxo-2'-deoxyguanosine 5'-triphosphate (8-oxo-dGTP) and 2-hydroxy-2'-deoxyadenosine 5'-triphosphate (2-OH-dATP) and thus protects cells from damage caused by their misincorporation into DNA. In the present study, we established MTH1-null mouse embryo fibroblasts that were highly susceptible to cell dysfunction and death caused by exposure to H2O2, with morphological features of pyknosis and electron-dense deposits accumulated in mitochondria. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 44 publications
(41 reference statements)
4
95
1
1
Order By: Relevance
“…Nakabeppu and his colleagues reported that both the 8-OH-dGTPase and 2-OH-dATPase activities of MTH1 contributed to the suppression of H 2 O 2 -induced mitochondrial dysfunction and cell death [37].…”
Section: Discussionmentioning
confidence: 99%
“…Nakabeppu and his colleagues reported that both the 8-OH-dGTPase and 2-OH-dATPase activities of MTH1 contributed to the suppression of H 2 O 2 -induced mitochondrial dysfunction and cell death [37].…”
Section: Discussionmentioning
confidence: 99%
“…Z-VAD-fmk efficiently suppressed staurosporine-induced cell death, which is dependent on caspases (Yoshimura et al, 2003), but did not suppress menadione-induced death (Supplementary Figure S4). We thus concluded that the menadione-induced cell death was independent of caspase activity.…”
Section: Establishment Of Ogg1mentioning
confidence: 99%
“…No alteration in the nuclear structure was observed (data not shown), whereas mitochondrial cristae in OGG1-null and Nu-hOGG1 MEFs were highly degenerated and electron-dense deposits (EDDs), which are the hallmark of mitochondrial dysfunction under oxidative damage (Yoshimura et al, 2003), had accumulated in À/À MEFs, with a P-value o0.05. (B) Structural comparison of hOGG1 proteins.…”
Section: Establishment Of Ogg1mentioning
confidence: 99%
See 1 more Smart Citation
“…3b), even though these compounds displayed the same degree of MTH1-inhibitory activities as NPD7155 and NPD9948 in vitro (Supplementary Table S1). It has been reported that MTH1 plays a crucial role in preventing incorporation of oxidized nucleotides into nuclear and mitochondrial DNA, allaying subsequent DNA damage 35 . Therefore, we examined the effects of our MTH1 inhibitors on 8-oxo-2ʹ -deoxyguanosine (8-oxo-dG) levels in DNA.…”
Section: Identification Of New Mth1 Inhibitors To Identify New Mth1 mentioning
confidence: 99%